Conduction system pacing versus biventricular pacing in heart failure with reduced ejection fraction and electrical dyssynchrony - Ammar, Ahmed; Elewa, Ahmed; Emam, Amr Y.; Sharief, Mohamed; Kamel, Omnia (Frontiers in Cardiovascular Medicine, 2024)
Biventricular pacing (BiVP) has been the cornerstone of cardiac resynchronization therapy (CRT) in the management of symptomatic heart failure patients with reduced ejection fraction (HFrEF) and electrical dyssynchrony despite guideline-directed medical therapy (GDMT). However, BiVP has some limitations, including technical difficulties and high non-response rates. Conduction system pacing encompassing His bundle pacing (HBP) and left bundle branch area pacing (LBBAP) has recently emerged as a promising alternative to CRT in this group of patients. In this review, we explore the current evidence, guidelines, limitations, gaps in knowledge, and ongoing trials comparing CSP and BiVP for the management of HFrEF with electrical dyssynchrony.